CERTIFICATE OF ACCREDITATION BACHELOR OF SOCIAL SCIENCES IN SOCIAL WORK WITH HONOURS (MQA/FA9695)(2017) - Jasmine, Jugah
MALAYSIAN QUALIFICATION AGENCY- CERTIFICATE OF ACCREDITATION BACHELOR OF SOCIAL SCIENCES IN SOCIAL WORK WITH HONOURS (MQA/FA9695), FACULTY OF SOCIAL SCIENCES AND HUMANITIES